Understanding pathways to stimulant use: a mixed-methods examination of the individual, social and cultural factors shaping illicit stimulant use across Europe (ATTUNE): study protocol. Issue 8 (10th August 2019) - Rosenkranz, Moritz; O'Donnell, Amy; Verthein, Uwe; Zurhold, Heike; Addison, Michelle; Liebregts, Nienke; Rowicka, Magdalena; Barták, Miroslav; Petruželka, Benjamin; Kaner, Eileen FS; Martens, Marcus-Sebastian
Abstract : Introduction: Amphetamine-type stimulants (ATS) including amphetamine, methylenedioxymethamphetamine/'ecstasy', methamphetamine, synthetic cathinones and 'Ritalin' are the second most commonly used illicit drugs globally. Yet, there is little evidence on which factors are associated with the development of different patterns of ATS use over the life course. This study aims to examine which individual, social and environmental factors shape different pathways and trajectories of ATS consumption. The study will be conducted in five European countries: Germany, the Netherlands, Poland, Czech Republic and the UK. Methods and analysis: We will use a sequential mixed-methods study design to investigate the multiple factors (familial, social and occupational situation, critical life events, general risk behaviour, mental and physical health, satisfaction with life) that shape individual ATS use pathways. A systematic literature review will be performed to provide an overview of the current academic literature on the topic. In module 1, qualitative semistructured interviews (n=ATS users and non-users) will be conducted to explore individual experiences of, and perspectives on, dynamics of change in stimulant consumption patterns. In module 2, structured questionnaires (n=2000 ATS users and non-users) will be administered via tablet computers to validate and enhance the generalisability of the interview findings. Data integration will take place at two key points. First, during the study, where the findings from the first qualitative interviews will inform the design of the structured questionnaire. Second, at the end of the study, where mixed methods data will be brought together to generate an in-depth, contextualised understanding of the research topic. Ethics and dissemination: The study has been approved by the respective responsible ethics committee in each participating country. Data will be treated confidentially to ensure participants' anonymity. Findings will be disseminated in peer-reviewed scientific journals, national and international conferences, and in briefings for policy and practice.